Digitalization of Forestry Museum Visiting Services Through the Implementation of a Reservation and Scheduling Platform - Jonser Steven Rajali Manik; Asa Yuaziva; Icha Maulidya; Siti Farah Fakhirah; Ridwan Siskandar (Journal of Applied Science, Technology & Humanities | JASTH, 2026)
This research is motivated by the Forestry Museum’s manual reservation process, resulting in irregular schedules and difficulties in managing visitor data. This research aims to build a digital reservation and scheduling platform from scratch using the Prototyping method supported by the Laravel, AJAX, and MySQL frameworks. Functional testing used the Black-Box Testing method, while user experience testing used the System Usability Scale (SUS). The Black Box Testing results showed a 100% success rate. The usability evaluation resulted in an average SUS score of 84.5 placing the system in the Acceptable category. Performance testing resulted in an average visitor form submission time of 0.34 seconds and admin decision execution time of 6.95 seconds, proving the system is capable of processing every data transaction instantly from a technical perspective, thus supporting the smooth flow of overall reservation confirmation. The systems meets the museum’s needs and is easy to use.